Καινοτόμος θερμοδυναμική ανάλυση αυθόρμητου ισοβαρούς μετασχηματισμού - Κούρτελλος, Γιώργος (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
This thesis aims to study a binary metal alloy with respect to classification of controlled mechanical properties.The components of the alloy under study are insoluble to each other and one of them presents allotropy.Since the microstructure of the alloy is formed by equilibrium thermal treatment processes and not only, the student is required after selecting a representative alloy to meet the following goals:To study various modes of composition through conventional methods.To justify any relevant restrictions on the homogenization of the microstructure of the alloy.To illustrate how to achieve the interaction of allotrope phases through the possibility of coexistence.To analyze in detail and by association, through the macroscopic properties of the phases, and demonstrate through modeling or theoretical approaches that a spontaneous transformation can equitably determine how interaction of allotrope phases.To illustrate how the proposed interaction can be used to homogenize the microstructure of the alloy.
Keywords: Μetal alloy; Spontaneous transformation; Μεταλλικό κράμα; Ισοβαρής μετασχηματισμός